Water-resistant catalyst as well as preparation and application thereof

By loading the cobalt precursor on the manganese salt hydrothermal precursor and calcining the sea urchin-shaped manganese dioxide substrate, the problem of reducing catalyst activity in water-containing flue gas and exhaust gas treatment is solved, and the effect of efficient treatment of Cl-VOCs in an aqueous environment is achieved.

CN119500173AActive Publication Date: 2025-02-25TIANJIN UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411596959.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-25
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

When treating water-containing flue gas and exhaust gas, the catalyst activity is reduced, the reaction is not thorough, the product is contaminated, and pre-dehydration treatment is required, which extends the treatment cycle and increases costs.

Method used

A water-resistant catalyst is used to obtain a precursor through hydrothermal heat in water through manganese salt and template agent, and then a cobalt precursor is supported on the manganese precursor, and a composite material supported on a sea urchin-like manganese dioxide substrate is obtained.

Benefits of technology

The water-resistant catalyst exhibits excellent catalytic activity and good water resistance in an aqueous environment. It can effectively treat Cl-VOCs at low ozone amounts, reduce the cost of ozone addition, avoid pre-dehydration treatment steps, and improve the treatment efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500173A_ABST
    Figure CN119500173A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of VOCs waste gas treatment, in particular to a water-resistant catalyst as well as preparation and application thereof. The invention provides a preparation method of a water-resistant catalyst. The preparation method comprises the following steps: mixing manganese salt and a template agent A in water, and performing hydrothermal treatment to obtain a precursor A; mixing the precursor A, cobalt salt and a template agent B in water, and performing hydrothermal treatment to obtain a precursor B; calcining the precursor B to obtain the water-resistant catalyst. According to the cobaltosic oxide composite material which is prepared by firstly preparing a manganese precursor, loading a cobalt precursor on the manganese precursor and finally calcining and takes sea-urchin-shaped manganese dioxide as a substrate and is loaded on the substrate, which is provided by the invention, the cobaltosic oxide composite material is proved to be capable of carrying out catalytic oxidation treatment on Cl-VOCs under a low ozone amount in a water-containing environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of VOCs waste gas treatment, and in particular to a water-resistant catalyst and preparation and application thereof. Background Art

[0002] At present, there are many methods for treating flue gas and waste gas containing chlorine volatile organic compounds (Cl-VOCs), including preventive measures to prevent the leakage of flue gas containing Cl-VOCs, such as changing operating conditions, replacing raw materials and replacing equipment. And mandatory measures for terminal control, including destruction and recovery methods for removing Cl-VOCs; the destruction methods include catalytic oxidation and biofiltration, and the recovery methods include absorption, adsorption, condensation and membrane separation.

[0003] Catalytic oxidation technology can completely convert Cl-VOCs in flue gas / waste gas into small molecules such as water, hydrogen chloride, carbon dioxide, etc. that are non-toxic or slightly toxic and easy to separate and collect. At the same time, the operation is relatively simple. Compared with the combustion method, the temperature required for the catalytic oxidation method can be reduced to below 400°C, achieving the complete conversion of Cl-VOCs and producing fewer secondary pollutants. It has higher selectivity, so it is often used to remove Cl-VOCs in flue gas and waste gas. Existing technologies for catalytic oxidation of Cl-VOCs include oxygen catalytic oxidation and ozone catalytic oxidation. It is worth noting that compared with other oxidation treatment technologies that require high temperature or high pressure conditions, ozone catalytic oxidation technology is more widely used because it can carry out Cl-VOCs oxidation reactions at lower temperatures (below 120°C).

[0004] However, in the actual treatment of flue gas and waste gas catalytic oxidation, a class of problems often arises. For example, the water content in the flue gas of domestic waste incineration can reach 5% vol, and the waste gas of industrial production processes often contains a high water vapor content. Because water has a high adsorption energy, the presence of water usually leads to competitive reactions, and then the overall reaction activity is reduced. Specifically: under oxygen catalytic oxidation reaction conditions above 300°C, the reaction activity usually decreases by 5-30%; under ozone catalytic oxidation reaction conditions below 200°C, the reaction activity usually decreases by 10-80%. Water-containing conditions lead to catalyst deactivation, incomplete catalytic reaction, and greater product pollution.

[0005] It can be found that the treatment of water-containing flue gas and waste gas is more difficult. Therefore, the common means of treating water-containing flue gas can refer to the Chinese patent with publication number CN111632462A, which discloses a method for treating water-containing flue gas from steel slag: this method first uses a wet method to roughly remove dust and cool the flue gas, remove part of the water vapor and large particles of smoke in the flue gas, and then uses sonication, spraying and dehydration treatment to perform secondary fine dust removal. In other words, the usual treatment of water-containing flue gas requires preliminary dehydration treatment and then subsequent treatment steps to avoid the impact of increased water content. This operation undoubtedly prolongs the flue gas treatment cycle and will increase the processing cost in actual industrial production. Therefore, it is in line with current development requirements to find a catalyst that can still ensure the efficiency of flue gas and waste gas treatment in a water-containing environment. Summary of the invention

[0006] The present invention aims to overcome the defects of large ozone dosage and water deactivation in the existing Cl-VOCs ozone catalytic oxidation removal technology in the prior art, and provides a water-resistant catalyst and its preparation and application to overcome the above defects.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a water-resistant catalyst, comprising:

[0009] S1, manganese salt and template A are mixed in water and then hydrothermally prepared to obtain precursor A;

[0010] Precursor A, cobalt salt and template B obtained in S2 and S1 are mixed in water and then hydrothermally prepared to obtain precursor B;

[0011] The precursor B obtained in S3 and S2 is calcined to obtain a water-resistant catalyst.

[0012] The present application first prepares a manganese-containing precursor, and then loads a cobalt precursor on the manganese precursor. After calcination, a water-resistant catalyst can be obtained. The water-resistant catalyst includes a sea urchin-shaped manganese dioxide substrate and cobalt tetroxide loaded on the manganese dioxide substrate; Co is grown on the surface of the sea urchin-shaped oxide, with manganese oxide as the dominant catalyst activity. The water-resistant catalyst with a special structure prepared by the present application scheme has been proven to be able to catalytically oxidize Cl-VOCs under low ozone levels in an aqueous environment. In addition, after the water-resistant catalyst provided by the present application combines manganese oxide and cobalt oxide, its water resistance is on par with cobalt oxide, and the amount of ozone is lower than that of manganese oxide, showing significant technological progress.

[0013] Preferably, in S1, the hydrothermal temperature is 100-110° C., and the hydrothermal time is 6-12 h.

[0014] Further preferably, in S1, the hydrothermal temperature is 100° C., and the hydrothermal time is 10 h.

[0015] Preferably, in S2, the hydrothermal temperature is 120-130° C., and the hydrothermal time is 10-16 h.

[0016] Further preferably, in S2, the hydroheating temperature is 120° C., and the hydroheating time is 10 h.

[0017] Preferably, in S3, the calcination temperature is 300-400°C, the calcination time is 2-3h, and the calcination heating rate is 1-5°C / min.

[0018] Further preferably, in S3, the calcination temperature is 350°C, the calcination time is 2h, and the calcination heating rate is 1°C / min.

[0019] Preferably, in S1, the template A is a sulfuric acid aqueous solution with a concentration of ≥98wt%.

[0020] Preferably, in S1, the dosage ratio between manganese in the manganese salt and the template A is 8 mmol: (1-5) mL.

[0021] More preferably, in S1, the dosage ratio between manganese in the manganese salt and the template A is 8 mmol:(1-3) mL.

[0022] Further preferably, in S1, the dosage ratio between manganese in the manganese salt and the template A is 8 mmol:2 mL.

[0023] Preferably, in S2, the template B is urea and ammonium fluoride.

[0024] Preferably, the molar ratio of cobalt, ammonium fluoride and urea in the cobalt salt is 1:(5-6):(4-5).

[0025] Further preferably, the molar ratio of cobalt, ammonium fluoride and urea in the cobalt salt is 1:6:5.

[0026] Preferably, the cobalt salt is one or more of cobalt nitrate, cobalt chloride and cobalt acetate.

[0027] Preferably, the manganese salt is one or more of potassium permanganate, manganese sulfate and manganese chloride.

[0028] Preferably, the molar ratio between the cobalt in the cobalt salt and the manganese in the manganese salt is (3-5):8.

[0029] Further preferably, the molar ratio between the cobalt in the cobalt salt and the manganese in the manganese salt is 4:8.

[0030] The present invention also provides a water-resistant catalyst, comprising a sea urchin-shaped manganese dioxide substrate and cobalt oxide supported on the manganese dioxide substrate; based on the weight of the water-resistant catalyst, the loading amount of the cobalt oxide is 7.0-19.8wt%.

[0031] The present invention also provides the water-resistant catalyst prepared by the above preparation method or the use of the above water-resistant catalyst in treating Cl-VOCs in water-containing flue gas / waste gas.

[0032] Preferably, the method for treating Cl-VOCs in water-containing flue gas / waste gas with the water-resistant catalyst is as follows: the water-resistant catalyst is placed in the water-containing flue gas / waste gas to carry out ozone catalytic oxidation reaction to achieve Cl-VOCs conversion, and harmless exhaustible gas is obtained after deacidification.

[0033] Preferably, the water-resistant catalyst can treat Cl-VOCs with a water content of (0.5% vol]) by ozone catalytic oxidation reaction.

[0034] Further preferably, the water-resistant catalyst can treat Cl-VOCs with a water content of [3% vol, 5% vol] by ozone catalytic oxidation reaction.

[0035] Preferably, during the ozone catalytic oxidation reaction, the molar ratio of ozone to Cl-VOCs in water-containing flue gas / waste gas is (2.5-12.5):1.

[0036] Further preferably, during the ozone catalytic oxidation reaction, the molar ratio of ozone to Cl-VOCs in water-containing flue gas / waste gas is (6-12):1.

[0037] Further preferably, during the ozone catalytic oxidation reaction, the molar ratio of ozone to Cl-VOCs in water-containing flue gas / waste gas is (6-8):1.

[0038] Therefore, the present invention has the following beneficial effects:

[0039] (1) The composite material provided by the present invention, which comprises first preparing a manganese precursor, loading a cobalt precursor on the manganese precursor, and finally calcining to obtain a sea urchin-shaped manganese dioxide substrate and cobalt tetroxide loaded on the substrate, has been proven to be able to catalytically oxidize Cl-VOCs under low ozone conditions in an aqueous environment.

[0040] (2) The present invention has discovered that the water-resistant catalyst has excellent catalytic activity and good water resistance, and can be directly used in the catalytic ozone oxidation treatment of Cl-VOCs in water-containing flue gas / waste gas without the need for a prior dehydration treatment step and then catalytic ozone oxidation, thereby greatly improving the treatment efficiency.

[0041] (3) When the water-resistant catalyst provided by the present invention is used to treat Cl-VOCs, a Cl-VOCs conversion rate of more than 90% can be achieved when the ozone molar ratio is equal to 6, thereby effectively reducing the cost of ozone addition.

[0042] (4) When the water-resistant catalyst provided by the present invention is applied to Cl-VOCs in water-containing flue gas / waste gas, the water-resistant catalyst exhibits an obvious water-promoting effect, and can replace part of the ozone with water at a low ozone concentration to generate strong oxidizing free radicals such as hydroxyl groups. It can reduce the ozone dosage while completely mineralizing dichloromethane, which can effectively reduce the catalytic cost and has practical application and promotion value.

[0043] (5) When the water-resistant catalyst provided by the present invention is used in the treatment of water-containing Cl-VOCs flue gas, it can maintain high activity and long-term stability, and can achieve water resistance at 120°C and below, with lower requirements for catalytic equipment.

[0044] (6) The water-resistant catalyst provided by the present invention can enhance the activation effect of water on the catalyst surface, convert water molecules into strong oxidizing free radicals such as hydroxyl groups to participate in the oxidation reaction, thereby hindering the condensation of water in the catalyst pores and the impact on the acidic sites, preventing the catalyst from being poisoned by water; and achieving the promotion of catalytic activity by water at low water content.

[0045] (7) After the water-resistant catalyst provided by the present invention combines manganese oxide and cobalt oxide, its water resistance is equal to that of cobalt oxide, and the amount of ozone is lower than that of manganese oxide, which shows a significant technological progress. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is the XRD diagram of the water-resistant catalyst prepared in Example 1.

[0047] Figure 2 This is a diagram showing the conversion effect of dichloromethane catalytically oxidized by the water-resistant catalyst prepared in Example 1 of the present invention at different ozone concentrations, wherein the ozone molar ratio is the molar ratio of ozone to Cl-VOCs in water-containing flue gas / waste gas.

[0048] Figure 3 The diagram shows the conversion effect of dichloromethane catalytically oxidized by the water-resistant catalyst prepared in Examples 2 to 4 of the present invention at different ozone concentrations, wherein the ozone molar ratio is the molar ratio of ozone to Cl-VOCs in water-containing flue gas / waste gas.

[0049] Figure 4 The diagram is a diagram showing the conversion effect of dichloromethane catalytically oxidized by the water-resistant catalysts prepared in Comparative Examples 1 to 5 of the present invention at different ozone concentrations, wherein the ozone molar ratio is the molar ratio of ozone to Cl-VOCs in water-containing flue gas / waste gas.

[0050] Figure 5The SEM structures of Example 1 and Comparative Example 3 prepared in the present invention are shown.

[0051] Figure 6 This is a dry-wet comparison chart of the ozone-catalyzed oxidation of dichloromethane using the water-resistant catalysts prepared in Examples 1 to 4 of the present invention.

[0052] Figure 7 This is a dry-wet comparison diagram of the ozone-catalyzed oxidation of dichloromethane using the water-resistant catalysts prepared in Comparative Examples 1 to 5 of the present invention.

[0053] Figure 8 The figure is a diagram showing the water promotion effect of the water-resistant catalyst prepared in Example 1 during ozone catalytic oxidation under 143 ppm ozone concentration (the two columns in each stage are the average integrated areas of TCM (left) and CT (right) detected by GC spectrum, where TCM is chloroform and CT is carbon tetrachloride).

[0054] Fig. 9 The diagram is a diagram of the water promotion effect of the catalyst prepared in Example 1 during the ozone catalytic oxidation process under 240 ppm ozone concentration (the two columns in each stage are the average integrated areas of TCM (left) and CT (right) detected by GC spectrum, where TCM is chloroform and CT is carbon tetrachloride).

[0055] Fig.10 The diagram is a diagram of the water promotion effect of the catalyst prepared in Example 2 during the ozone catalytic oxidation process under 240 ppm ozone concentration (the two columns in each stage are the average integrated areas of TCM (left) and CT (right) detected by GC spectrum, where TCM is chloroform and CT is carbon tetrachloride).

[0056] Fig.11 This is a diagram of the long-term dichloromethane conversion effect under the conditions of 600 ppm ozone concentration and 3% vol water vapor in Example 1 (the two columns in each stage are the average integrated areas of TCM (left) and CT (right) detected by GC spectrum, where TCM is trichloromethane and CT is carbon tetrachloride).

[0057] Fig.12 This is a diagram of the long-term dichloromethane conversion effect under the conditions of 600 ppm ozone concentration and 3% vol water vapor in Example 2 (the two columns in each stage are the average integrated areas of TCM (left) and CT (right) detected by GC spectrum, where TCM is trichloromethane and CT is carbon tetrachloride). DETAILED DESCRIPTION

[0058] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0059] [Example]

[0060] Example 1

[0061] (1) Dissolve 1.2614 g potassium permanganate (8 mmol) and 2 mL 98 wt% concentrated sulfuric acid in 75 mL deionized water, stir thoroughly and ultrasonicate for 30 min to obtain a mixed solution.

[0062] (2) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 100 °C for 10 h.

[0063] (3) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry in a forced air drying oven at 100° C. for 12 h to obtain a powder dry solid.

[0064] (4) The powdered dry solid was mixed with 1.1641 g (4 mmol) of cobalt nitrate hexahydrate, 1.2016 g (20 mmol) of urea and 0.888 g (24 mmol) of ammonium fluoride in 72 mL of deionized water, stirred thoroughly and subjected to ultrasonic treatment for 30 min to obtain a mixed solution.

[0065] (5) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 120 °C for 10 h.

[0066] (6) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry it in a forced air drying oven at 100° C. for 10 h to obtain a powder dry solid.

[0067] (7) The dry powdered solid was calcined in a tube furnace under a static air atmosphere at a heating rate of 1°C / min at a final temperature of 350°C for 2 h to obtain the catalyst powder H-MnO2@Co3O4-4.

[0068] The XRD spectrum of the prepared H-MnO2@Co3O4-4 is shown in Figure 1 shown by Figure 1 It can be seen that the Co peak is weaker and has higher dispersion, while the Mn peak is more obvious and has outstanding activity.

[0069] Example 2

[0070] (1) Dissolve 1.2614 g potassium permanganate (8 mmol) and 2 mL 98 wt% concentrated sulfuric acid in 75 mL deionized water, stir thoroughly and ultrasonicate for 30 min to obtain a mixed solution.

[0071] (2) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 100 °C for 6 h.

[0072] (3) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry in a forced air drying oven at 100° C. for 12 h to obtain a powder dry solid.

[0073] (4) The powdered dry solid was mixed with 1.1641 g (4 mmol) of cobalt nitrate hexahydrate, 1.2016 g (20 mmol) of urea and 0.888 g (24 mmol) of ammonium fluoride in 72 mL of deionized water, stirred thoroughly and subjected to ultrasonic treatment for 30 min to obtain a mixed solution.

[0074] (5) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 120 °C for 10 h.

[0075] (6) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry it in a forced air drying oven at 100° C. for 10 h to obtain a powder dry solid.

[0076] (7) The dry powdered solid was calcined in a tubular furnace under a static air atmosphere at a heating rate of 1°C / min at a final temperature of 350°C for 2 h to obtain the catalyst powder S-MnO2@Co3O4-4.

[0077] Example 3

[0078] (1) Dissolve 1.2614 g potassium permanganate (8 mmol) and 2 mL 98 wt% concentrated sulfuric acid in 75 mL deionized water, stir thoroughly and ultrasonicate for 30 min to obtain a mixed solution.

[0079] (2) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 100 °C for 12 h.

[0080] (3) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry in a forced air drying oven at 100° C. for 12 h to obtain a powder dry solid.

[0081] (4) The powdered dry solid was mixed with 0.8731 g (3 mmol) of cobalt nitrate hexahydrate, 1.2016 g (20 mmol) of urea and 0.888 g (24 mmol) of ammonium fluoride in 72 mL of deionized water, stirred thoroughly and subjected to ultrasonic treatment for 30 min to obtain a mixed solution.

[0082] (5) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 120 °C for 10 h.

[0083] (6) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry it in a forced air drying oven at 100° C. for 10 h to obtain a powder dry solid.

[0084] (7) The dry powdered solid was calcined in a tube furnace under a static air atmosphere at a heating rate of 1°C / min at a final temperature of 350°C for 2 h to obtain the catalyst powder H-MnO2@Co3O4-3.

[0085] Example 4

[0086] (1) Dissolve 1.2614 g potassium permanganate (8 mmol) and 2 mL 98 wt% concentrated sulfuric acid in 75 mL deionized water, stir thoroughly and ultrasonicate for 30 min to obtain a mixed solution.

[0087] (2) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 100 °C for 12 h.

[0088] (3) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry in a forced air drying oven at 100° C. for 12 h to obtain a powder dry solid.

[0089] (4) The powdered dry solid was mixed with 1.4551 g (5 mmol) of cobalt nitrate hexahydrate, 1.2016 g (20 mmol) of urea and 0.888 g (24 mmol) of ammonium fluoride in 72 mL of deionized water, stirred thoroughly and subjected to ultrasonic treatment for 30 min to obtain a mixed solution.

[0090] (5) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 120 °C for 10 h.

[0091] (6) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry it in a forced air drying oven at 100° C. for 10 h to obtain a powder dry solid.

[0092] (7) The dry powdered solid was calcined in a tube furnace under a static air atmosphere at a heating rate of 1°C / min at a final temperature of 350°C for 2 h to obtain catalyst powder H-MnO2@Co3O4-5.

[0093] [Comparative Example]

[0094] Comparative Example 1

[0095] (1) Dissolve 1.2614 g potassium permanganate (8 mmol) and 2 mL 98 wt% concentrated sulfuric acid in 75 mL deionized water, stir thoroughly and ultrasonicate for 30 min to obtain a mixed solution.

[0096] (2) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 100 °C for 12 h.

[0097] (3) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry in a forced air drying oven at 100° C. for 12 h to obtain a powder dry solid.

[0098] (4) The powdered dry solid was mixed with 0.2910 g (3 mmol) of cobalt nitrate hexahydrate, 1.2016 g (20 mmol) of urea and 0.888 g (24 mmol) of ammonium fluoride in 72 mL of deionized water, stirred thoroughly and subjected to ultrasonic treatment for 30 min to obtain a mixed solution.

[0099] (5) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 120 °C for 10 h.

[0100] (6) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry it in a forced air drying oven at 100° C. for 10 h to obtain a powder dry solid.

[0101] (7) The dry powdered solid was calcined in a tube furnace under a static air atmosphere at a heating rate of 1°C / min at a final temperature of 350°C for 2 h to obtain the catalyst powder H-MnO2@Co3O4-1.

[0102] Comparative Example 2

[0103] (1) Dissolve 1.2614 g potassium permanganate (8 mmol) and 2 mL 98 wt% concentrated sulfuric acid in 75 mL deionized water, stir thoroughly and ultrasonicate for 30 min to obtain a mixed solution.

[0104] (2) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 100 °C for 12 h.

[0105] (3) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry in a forced air drying oven at 100° C. for 12 h to obtain a powder dry solid.

[0106] (4) The powdered dry solid was mixed with 0.5821 g (2 mmol) of cobalt nitrate hexahydrate, 1.2016 g (20 mmol) of urea and 0.888 g (24 mmol) of ammonium fluoride in 72 mL of deionized water, stirred thoroughly and subjected to ultrasonic treatment for 30 min to obtain a mixed solution.

[0107] (5) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 120 °C for 10 h.

[0108] (6) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry it in a forced air drying oven at 100° C. for 10 h to obtain a powder dry solid.

[0109] (7) The dry powdered solid was calcined in a tube furnace under a static air atmosphere at a heating rate of 1°C / min at a final temperature of 350°C for 2 h to obtain catalyst powder H-MnO2@Co3O4-2.

[0110] Comparative Example 3

[0111] (1) 1.1641 g (4 mmol) of cobalt nitrate hexahydrate, 1.2016 g (20 mmol) of urea, and 0.888 g (24 mmol) of ammonium fluoride were mixed in 72 mL of deionized water, stirred thoroughly, and then ultrasonicated for 30 min to obtain a mixed solution.

[0112] (2) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 120°C for 10 h.

[0113] (3) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry in a forced air drying oven at 100° C. for 12 h to obtain a powder dry solid.

[0114] (4) The powdered dry solid was dissolved with 1.2614 g potassium permanganate (8 mmol) and 2 mL 98 wt % concentrated sulfuric acid in 75 mL deionized water, stirred thoroughly and ultrasonicated for 30 min to obtain a mixed solution.

[0115] (5) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 100 °C for 12 h.

[0116] (6) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry it in a forced air drying oven at 100° C. for 10 h to obtain a powder dry solid.

[0117] (7) The dry powdered solid was calcined in a tube furnace under a static air atmosphere at a heating rate of 1°C / min at a final temperature of 350°C for 2 h to obtain the catalyst powder Co3O4@MnO2.

[0118] Comparative Example 4

[0119] (1) 1.1641 g (4 mmol) of cobalt nitrate hexahydrate, 1.2016 g (20 mmol) of urea, and 0.888 g (24 mmol) of ammonium fluoride were mixed in 72 mL of deionized water, stirred thoroughly, and then ultrasonicated for 30 min to obtain a mixed solution.

[0120] (2) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 120°C for 10 h.

[0121] (3) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry in a forced air drying oven at 100° C. for 12 h to obtain a powder dry solid.

[0122] (4) The dry powdered solid was calcined in a tube furnace in a static air atmosphere at a heating rate of 1°C / min at a final temperature of 350°C for 2 h to obtain a catalyst powder Co3O4.

[0123] Comparative Example 5

[0124] (1) Dissolve 1.2614 g potassium permanganate (8 mmol) and 2 mL 98 wt% concentrated sulfuric acid in 75 mL deionized water, stir thoroughly and ultrasonicate for 30 min to obtain a mixed solution.

[0125] (2) The mixed solution was placed in a 100 mL hydrothermal reactor and subjected to hydrothermal reaction in an oven at 100 °C for 12 h.

[0126] (3) After cooling to room temperature, centrifuge and wash to obtain a wet powder solid, and dry in a forced air drying oven at 100° C. for 12 h to obtain a powder dry solid.

[0127] (4) The dry powdered solid was calcined in a tube furnace in a static air atmosphere at a heating rate of 1°C / min at a final temperature of 350°C for 2 h to obtain catalyst powder MnO2.

[0128]

Application of water-resistant catalyst

[0129] Take 0.05 g of the catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 5 (the following application examples are based on this dosage) and conduct subsequent application experiments on this basis.

[0130] When dichloromethane (DCM) is used as a Cl-VOCs model compound, the performance of the above catalyst in catalyzing ozone catalytic oxidation of Cl-VOCs under different ozone concentrations in a low-temperature dry gas phase is explored; the specific steps are: placing the catalysts prepared corresponding to Examples 1 to 4 and Comparative Examples 1 to 5 in a dry flue gas environment, adjusting different sampling concentrations, using the catalyst to perform ozone catalytic oxidation reaction on Cl-VOCs containing a dichloromethane concentration of 100 ppm, and obtaining a dischargeable gas after deacidification.

[0131] The corresponding catalyst bed volume space velocity ratio and temperature when the catalysts prepared under different schemes are used are shown in Table 1.

[0132] Table 1 Catalyst bed parameters and heating temperatures when using different catalysts

[0133] product Catalyst bed volume space velocity ratio Catalyst bed temperature <![CDATA[H-MnO2@Co3O4-1]]> <![CDATA[20000h -1 ]]> 120℃ <![CDATA[H-MnO2@Co3O4-2]]> <![CDATA[20000h -1 ]]> 120℃ <![CDATA[H-MnO2@Co3O4-3]]> <![CDATA[20000h -1 ]]> 120℃ <![CDATA[H-MnO2@Co3O4-4]]> <![CDATA[20000h -1 ]]> 120℃ <![CDATA[H-MnO2@Co3O4-5]]> <![CDATA[20000h -1 ]]> 120℃ <![CDATA[S-MnO2@Co3O4-4]]> <![CDATA[20000h -1 ]]> 120℃ <![CDATA[Co3O4@MnO2]]> <![CDATA[20000h -1 ]]> 120℃ <![CDATA[Co3O4]]> <![CDATA[20000h -1 ]]> 120℃ <![CDATA[MnO2]]> <![CDATA[20000h -1 ]]> 120℃

[0134] After the reaction was completed, gas chromatography was used to detect the conversion rate of dichloromethane in the process of ozone catalytic oxidation of dichloromethane. The test results are shown in Figures 2 to 4 .

[0135] The results show that the conversion rate of dichloromethane by ozone catalytic oxidation of the water-resistant catalyst prepared in Example 1 reaches more than 90% when the ozone molar ratio is equal to 6, and the conversion rate of dichloromethane by ozone catalytic oxidation of the water-resistant catalyst prepared in Example 2 reaches more than 90% when the ozone molar ratio is equal to 6. The conversion rate of dichloromethane by ozone catalytic oxidation of the catalyst prepared in Example 3 reaches more than 90% when the ozone molar ratio is equal to 6. The conversion rate of dichloromethane by ozone catalytic oxidation of the catalyst prepared in Example 4 reaches more than 90% when the ozone molar ratio is equal to 6. The conversion rate of dichloromethane by ozone catalytic oxidation of the catalyst prepared in Comparative Example 1 reaches more than 75% when the ozone molar ratio is equal to 6. The conversion rate of dichloromethane by ozone catalytic oxidation of the catalyst prepared in Comparative Example 2 reaches more than 85% when the ozone molar ratio is equal to 6. The conversion rate of dichloromethane by ozone catalytic oxidation of the catalyst prepared in Comparative Example 3 reaches more than 60% when the ozone molar ratio is equal to 6. The conversion rate of dichloromethane by ozone catalytic oxidation of the catalyst prepared in Comparative Example 4 reaches more than 80% when the ozone molar ratio is equal to 6. The conversion rate of dichloromethane by ozone catalytic oxidation of the catalyst prepared in Comparative Example 5 reaches more than 80% when the ozone molar ratio is equal to 6. Among them, when the ozone molar ratio is 6, the conversion efficiency of Example 1 is more than 90%; and when the ozone molar ratio is increased to 12, the conversion rate of Comparative Example 5 can reach more than 90%. Obviously, after Example 1 is compounded with cobalt oxide and manganese oxide, less ozone is consumed compared with a single manganese oxide (Comparative Example 5) to achieve a better dichloromethane conversion rate.

[0136] Analysis of the above data shows that Examples 1, 2 and Comparative Example 3 are water-resistant catalysts prepared with 4 mmol of Co added. The solution of this application is to grow Co on the surface of sea urchin-shaped oxides, with manganese oxide as the dominant catalyst activity. Due to the uniform growth of a certain amount of Co on the surface of manganese oxides, coupled with the influence of secondary hydrothermal treatment, the solid / hollow structure of Mn has little effect on the catalyst activity. Figure 5 It can be seen that the adsorption performance of Comparative Example 3 is reduced due to the loss of the excellent sea urchin-like structure of Mn, the active sites are reduced, and the conversion rate is reduced. Implementation cases 3, 4 and Comparative Examples 1 and 2 are water-resistant catalysts prepared with different Co addition amounts. As the Co content increases, the Co-Mn interaction is enhanced, the interface effect and ion exchange are promoted, and the activity is improved. When the Co addition amount increases to a certain value, Co will cover the Mn surface, thereby robbing Mn of its active dominance, and the activity will decrease instead.

[0137] Compared with the simple cobalt oxide and manganese oxide in Comparative Examples 4 and 5, the activities of Examples 1 and 2 are higher than any single metal catalyst due to their unique electronic interactions and synergistic effects between metals.

[0138] Application Example 2

[0139] From the results of Application Example 1, it can be seen that the water-resistant catalysts prepared in Examples 1 to 4 all exhibited good dichloromethane conversion rates under dry conditions. Therefore, this application example further explores this basis.

[0140] In actual application, it is often not only dry flue gas that is processed. In the face of complex working conditions that may arise in actual applications, this application example studies the effect of water-containing flue gas on the catalytic conversion efficiency of the catalyst. Specifically: Cl-VOCs flue gas containing 100ppm of dichloromethane is passed into an ozone catalytic oxidation unit equipped with a catalyst bed, and mixed with ozone with a concentration of 600ppm in the catalytic oxidation unit for reaction; the total gas volume is maintained at 100mL / min, and the acid is removed and discharged after the reaction. After reacting for three hours under dry conditions, 3%vol of water vapor is introduced and the reaction is continued for three hours. During the experiment, gas chromatography was used to detect the conversion rate of dichloromethane in the process of ozone catalytic oxidation of dichloromethane. The test results are shown in the figure. Figure 6-7 .

[0141] The results show that: Examples 1, 2, 4 and Comparative Example 4 showed obvious water-promoting effects after adding water, Example 3 showed more water resistance, and the activity of Comparative Examples 1, 2, 3, and 5 was affected to a certain extent by adding water. From the comparison results, it is known that Co is the main water-resistant component, and as the amount of Co added increases, the water-resistant benefit of Co is more fully exerted. Therefore, while maintaining a specific morphology, the addition of a certain amount of Co can fully exert the water resistance of Co metal without affecting the dominance of Mn activity, thereby improving the overall water resistance of the catalyst, which can be applied to actual scenarios such as domestic waste incineration. Among them, by comparing the data results of Example 1 and Comparative Example 4, it can be seen that after the compounding of cobalt oxide and manganese oxide in Example 1, its water resistance is still on par with that of single cobalt oxide.

[0142] Application Example 3

[0143] The water-resistant catalyst prepared in Example 1 (H-MnO2@Co3O4-4) was used to explore the water-promoting effect: Cl-VOCs flue gas containing dichloromethane with a concentration of 100 ppm was introduced into an ozone catalytic oxidation unit equipped with a catalyst bed, and the catalyst bed volume space velocity ratio was 20000h -1, mixed with ozone at a concentration of 143ppm in the catalytic oxidation unit to maintain a total gas volume of 100mL / min, and deacidified and discharged after the reaction. During the experiment, the operating conditions were changed every two hours, in the following chronological order: 120℃, dry flue gas; 120℃, 1%vol water vapor; 120℃, 3%vol water vapor; 120℃, 5%vol water vapor; 150℃, 5%vol water vapor; 150℃, 3%vol water vapor; 150℃, 1%vol water vapor; 150℃, dry flue gas. See the test results. Figure 8 .

[0144] The results show that the conversion rate of the H-MnO2@Co3O4-4 catalyst is increased from 50% to 51% under the conditions of 120°C, 143ppm ozone concentration and 1%vol water vapor, and the conversion rate can be increased to 54% under the conditions of 150°C and 1%vol water vapor, indicating that the water-resistant catalyst has high activity and still has strong water-resistant properties under low temperature and low ozone conditions.

[0145] Application Example 4

[0146] The ozone concentration was increased to further explore the water-promoting effect of the H-MnO2@Co3O4-4 catalyst: Cl-VOCs flue gas containing dichloromethane with a concentration of 100 ppm was passed into the ozone catalytic oxidation unit equipped with a catalyst bed, and the catalyst bed volume space velocity ratio was 20000h -1 , mixed with 240ppm ozone in the catalytic oxidation unit, maintaining a total gas volume of 100mL / min, and deacidification after the reaction. During the experiment, the operating conditions were changed every two hours, in the following order: 120℃, dry flue gas; 120℃, 1%vol water vapor; 120℃, 3%vol water vapor; 120℃, 5%vol water vapor; 150℃, 5%vol water vapor; 150℃, dry flue gas. Test results are shown in Fig. 9 .

[0147] The results show that the catalyst will be more sensitive to water activation reaction when the ozone concentration is increased to a certain level. Under the conditions of 120℃, 240ppm ozone concentration and 3%vol water vapor, the dichloromethane conversion rate increased from 74% to 79%; when the temperature was increased to 150℃ and the water vapor was increased to 5%vol, the dichloromethane conversion rate increased to 83%, indicating that the H-MnO2@Co3O4-4 catalyst can completely mineralize dichloromethane while reducing the ozone dosage after adding water vapor, effectively reducing the catalytic cost.

[0148] Application Example 5

[0149] The water resistance of S-MnO2@Co3O4-4 catalyst was explored: Cl-VOCs flue gas containing dichloromethane with a concentration of 100 ppm was passed into an ozone catalytic oxidation unit equipped with a catalyst bed. The catalyst bed volume space velocity ratio was 20000h -1 , mixed with ozone at a concentration of 230ppm in the catalytic oxidation unit to react, maintaining a total gas volume of 100mL / min, and deacidifying and discharging after the reaction. During the experiment, the operating conditions were changed every two hours, in the following chronological order: 120℃, dry flue gas; 120℃, 1%vol water vapor; 120℃, 3%vol water vapor; 120℃, 5%vol water vapor; 150℃, 5%vol water vapor; 150℃, 3%vol water vapor; 150℃, 1%vol water vapor; 150℃, dry flue gas. See the test results. Fig.10 .

[0150] The results show that the conversion rate of the catalyst is increased from 71% to 82% under the conditions of 120°C, 230ppm ozone concentration and 3%vol water vapor, and the conversion rate can be increased to 84% under the conditions of 150°C and 3%vol water vapor, indicating that the catalyst has high activity and still has strong water resistance under low temperature and low ozone conditions. After adding water vapor, it can reduce ozone dosage while completely mineralizing dichloromethane, effectively reducing the catalytic cost.

[0151] This result shows that the water-resistant catalysts prepared under different hydrothermal times in step (2) of the embodiment have similar performances, which proves that the hydrothermal time has little effect on the catalyst performance.

[0152] Application Example 6

[0153] The water-resistant catalysts prepared in Examples 1 and 2 were tested for long-term water resistance under ozone catalytic oxidation conditions: Cl-VOCs flue gas containing dichloromethane at a concentration of 100 ppm was introduced into an oxygen catalytic oxidation unit equipped with a catalyst bed, and mixed with ozone at a concentration of 230 ppm in the catalytic oxidation unit for reaction, with the total gas volume maintained at 100 mL / min, and deacidified after the reaction. Catalyst bed volume space velocity ratio 20000 h -1 The catalyst bed temperature is 120℃. After 1 hour, 3% vol water vapor is added to the flue gas. After the reaction, the acid is removed and discharged. The test results and specific working conditions are shown in Figure 11-12 .

[0154] The results show that H-MnO2@Co3O4-4 and S-MnO2@Co3O4-4 can maintain high efficiency and stability for a long time under 3% vol water vapor conditions, and manifest as a water-promoting effect.

Claims

1. A method for preparing a water-resistant catalyst, characterized in that: include: S1, manganese salt and template A are mixed in water and then hydrothermally prepared to obtain precursor A; Precursor A, cobalt salt and template B obtained in S2 and S1 are mixed in water and then hydrothermally prepared to obtain precursor B; The precursor B obtained in S3 and S2 is calcined to obtain a water-resistant catalyst.

2. The preparation method according to claim 1, characterized in that In S1, the hydrothermal temperature is 100-110°C, and the hydrothermal time is 6-12h; in S2, the hydrothermal temperature is 120-130°C, and the hydrothermal time is 10-16h; in S3, the calcination temperature is 300-400°C, the calcination time is 2-3h, and the calcination heating rate is 1-5°C / min.

3. The preparation method according to claim 1, characterized in that: In S1, the template A is a sulfuric acid aqueous solution with a concentration of ≥98wt%; in S2, the template B is urea and ammonium fluoride.

4. The preparation method according to claim 1 or 3, characterized in that: In the S1, the dosage ratio between the manganese in the manganese salt and the template A is 8 mmol: (1-5) mL.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The molar ratio between the cobalt in the cobalt salt and the manganese in the manganese salt is (3-5):

8.

6. The water-resistant catalyst prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The invention comprises a sea urchin-shaped manganese dioxide substrate and cobalt oxide supported on the manganese dioxide substrate; based on the weight of the water-resistant catalyst, the supported amount of the cobalt oxide is 7.0-19.8wt%.

7. Use of the water-resistant catalyst prepared by the preparation method according to any one of claims 1 to 5 or the water-resistant catalyst according to claim 6 in treating Cl-VOCs in water-containing flue gas / waste gas.

8. The use according to claim 7, characterized in that The method for treating Cl-VOCs in water-containing flue gas / waste gas with the water-resistant catalyst is as follows: the water-resistant catalyst is placed in the water-containing flue gas / waste gas for ozone catalytic oxidation reaction to achieve Cl-VOCs conversion, and harmless exhaustible gas is obtained after deacidification.

9. The use according to claim 7, characterized in that The water-resistant catalyst can treat Cl-VOCs with a water content of (0.5% vol] by ozone catalytic oxidation reaction.

10. The use according to claim 7, characterized in that During the ozone catalytic oxidation reaction, the molar ratio of ozone to Cl-VOCs in water-containing flue gas / waste gas is (2.5-12.5):1.

Citation Information

Patent Citations

  • Steel slag water-containing flue gas treatment method

    CN111632462A

  • Cobalt-manganese catalyst for eliminating volatile organic compounds by oxidization and preparation method thereof

    CN109364938A

  • Catalyst for treatment of CVOC by catalytic combustion method and preparation method thereof

    CN110624549A

  • Preparation method of high-photoelectrocatalysis cobaltosic oxide supported carbon fiber

    CN110841643A

  • Manganese-cobalt composite oxide catalyst for eliminating VOCs, preparation method and applications thereof

    CN111085218A